2020
DOI: 10.3390/tropicalmed5030110
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Assessment of Health Literacy and Health Status of Rohingya Refugees Living in Cox’s Bazar, Bangladesh Following the August 2017 Exodus from Myanmar: A Cross-Sectional Study

Abstract: Background: A survey was conducted among Rohingya refugees to assess their overall health literacy and health status. Methods: A questionnaire was developed to conduct face to face interviews among Rohingya refugees in Cox’s Bazar, Bangladesh in November–December 2017. Families were selected using convenience sampling from four large refugee camps. Results: Primary respondents aged 10–90 (median 32) years, 56% male, representing 1634 families were interviewed and provided data of themselves and 6268 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
(35 reference statements)
0
13
1
Order By: Relevance
“…Several international humanitarian organizations, local governments, and nongovernmental organizations have been providing temporary shelters, access to sanitation, and healthcare. When additional care is required, patients are transferred to local governmental medical college hospitals in Cox’s Bazar and Chittagong [ 6–8 ]. In the Cox’s Bazar Rohingya camp, overcrowding FDMN lack access to healthcare, nutrition, safe water, and proper sanitation.…”
mentioning
confidence: 99%
“…Several international humanitarian organizations, local governments, and nongovernmental organizations have been providing temporary shelters, access to sanitation, and healthcare. When additional care is required, patients are transferred to local governmental medical college hospitals in Cox’s Bazar and Chittagong [ 6–8 ]. In the Cox’s Bazar Rohingya camp, overcrowding FDMN lack access to healthcare, nutrition, safe water, and proper sanitation.…”
mentioning
confidence: 99%
“…Most of the FDMNs were involved with agricultural and farming activities (18%) or were children (22%) and housewives (40%) prior to coming to Bangladesh. The low health literacy among FDMNs was described in a recent publication [ 7 ]. Viral hepatitis particularly hepatitis C was common among FDMN in comparison with the host community.…”
Section: Discussionmentioning
confidence: 99%
“…The FDMNs share the limited local government health care system resources with the local Bangladeshis. A 2017 survey of FDMNs found poor health literacy and insufficient health care while living in Myanmar [ 7 ]. A recent review found that the Rohingya refugees are facing deprivation of basic health and other needs.…”
Section: Introductionmentioning
confidence: 99%
“…Two original articles focussed on the health of Rohingyas, among the most persecuted minorities in the world. One article assessed health literacy and health status of Rohingya refugees before their exodus to Bangladesh in 2017, showing that the majority (70%) of the 192 deaths that occurred in 1634 families in the year before their migration to Bangladesh occurred in men and 44% were claimed to be due to homicide [ 6 ]. A focussed survey involving 670 infants aged < 2 months showed that about 15% of children had watery or purulent discharge from their eyes [ 7 ]; although the study design did not include establishment of microbiological diagnosis, given the high likelihood of sexually transmitted infections among Rohingya refugees [ 8 ], some of these eye symptoms could be due to gonococcal ophthalmia neonatorum and, thus, deserve public health attention.…”
mentioning
confidence: 99%